2017
DOI: 10.1080/07399332.2017.1365867
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and experience of health professionals of female genital mutilation (FGM): A qualitative study in Iraqi Kurdistan Region

Abstract: We aimed to assess the knowledge, attitude, and experience of health professionals of female genital mutilation (FGM). The study involved content analysis of semistructured interviews with 21 health professionals. The participants had poor knowledge regarding different aspects of FGM including its types, prevalence, and complications as well as the existing legislation that prohibits FGM. They believed that FGM is mainly practiced for religious reasons and to reduce sexual desire/arousal. Health professionals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…This study revealed that the mothers or grandmothers usually decide to do FGM to the girls, a finding that agrees with other studies from Iraqi Kurdistan Region where the fathers and the men members of the family are usually not involved in taking the decision [15]. In most other settings such as East Ethiopia, mothers and grandmothers play a dominant role in deciding and organizing FGM for their daughters [21].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This study revealed that the mothers or grandmothers usually decide to do FGM to the girls, a finding that agrees with other studies from Iraqi Kurdistan Region where the fathers and the men members of the family are usually not involved in taking the decision [15]. In most other settings such as East Ethiopia, mothers and grandmothers play a dominant role in deciding and organizing FGM for their daughters [21].…”
Section: Discussionsupporting
confidence: 87%
“…The participants emphasized the terrible experience of going through FGM and the pain and the psychological effect of such experience. Going through the devastating experience of FGM or observing the practice at such a young age results in significant fear and other psychological effects in addition to the immediate consequences of pain and bleeding [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This factor is essential in providing adequate care because women exposed to FGC have professed a greater satisfaction and comfortability in discussing FGC with health workers with prior knowledge of FGC [63,64]. Not only have healthcare providers acknowledged communication challenges with FGC patients and a lack of formal training or protocols guide for FGC [56], there have been studies that acknowledge poor knowledge regarding different aspects of FGC among healthcare professionals [65]. However, some studies emphasized that healthcare professionals may require the confidence to talk about the subject due to insufficient knowledge, may lack the experience in handling patients with FGC, or may lack understanding of patient culture [53].…”
Section: Barriers In the Healthcare Systemmentioning
confidence: 99%